2020
DOI: 10.1371/journal.pone.0237965
|View full text |Cite
|
Sign up to set email alerts
|

No safe place: Prevalence and correlates of violence against conflict-affected women and girls in South Sudan

Abstract: Background Conflict and humanitarian crises increase the risk of both intimate partner violence and nonpartner sexual violence against women and girls. We measured the prevalence and risk factors of different forms of violence against women and girls in South Sudan, which has suffered decades of conflict, most recently in 2013. Methods A population-based survey was conducted among women aged 15-64 in three conflictaffected sites in South Sudan: Juba, Rumbek, and the Protection of Civilian Sites (PoCs) in Juba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 20 publications
5
55
2
Order By: Relevance
“…The qualitative research presented in this article informed the design of a household survey of men and women in three of the conflict-affected settings where the qualitative study was performed (Rumbek, Juba City, and Juba PoC sites). The results of the household survey, which are presented elsewhere ( Ellsberg et al, 2020 ; Murphy et al, 2020 ), reinforced the qualitative findings. The survey found that women and girls in South Sudan suffer some of the highest levels of physical and sexual violence in the world.…”
Section: Discussionsupporting
confidence: 64%
“…The qualitative research presented in this article informed the design of a household survey of men and women in three of the conflict-affected settings where the qualitative study was performed (Rumbek, Juba City, and Juba PoC sites). The results of the household survey, which are presented elsewhere ( Ellsberg et al, 2020 ; Murphy et al, 2020 ), reinforced the qualitative findings. The survey found that women and girls in South Sudan suffer some of the highest levels of physical and sexual violence in the world.…”
Section: Discussionsupporting
confidence: 64%
“…Over 60% of participants reported experiences with controlling behaviors, 25% with psychological abuse, and 28% with physical and/or sexual violence. These rates are similar to those reported by sample of Tanzanian adolescent and young women but lower than other samples of conflict-affected adolescent girls and women in South Sudan and the DRC [46][47][48]. Attitudes towards men's perpetration of violence against women is a factor known to influence IPV's acceptability, its overall incidence rate, and the responses of survivors and those close to them [49].…”
Section: Discussionsupporting
confidence: 76%
“…Studies have shown conflict-affected countries since 1990 have consistently higher maternal and child mortality rates than non-conflict countries and access to essential reproductive and maternal health services for poorer, less educated and rural-based families was considerably worse in conflict versus non-conflict countries [ 29 ]. Alarmingly high rates of sexual and gender-based violence with a strong association of mental health disorders, such as Post Traumatic Stress Disorder and Depression, have long been documented in several conflict-affected settings [ 30 , 31 ]. Women are disproportionately affected by the negative consequences of conflict-induced forced displacement [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yemeni women’s increased vulnerability has led to negative coping mechanisms such as early marriages and child labour. Restrictive marital practices, gender norms, and experiences of conflict were major drivers of both partner and non-partner violence in the conflict in South Sudan [ 31 ].…”
Section: Resultsmentioning
confidence: 99%